2012
DOI: 10.1002/adsc.201200043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite‐Gold(I)‐Catalyzed [2+2] Intermolecular Cycloaddition of Enol Ethers with N‐Allenylsulfonamides

Abstract: Addition of catalytic amounts of a phosphite‐based gold(I) catalyst efficiently triggers the intermolecular [2+2] cycloaddition of allenes and alkenes substituted by electron‐donor groups. The reaction is fast and furnishes cyclobutane derivatives in a stereoselective manner using low catalyst loadings. Besides, the same catalyst selectively affords homodimerization products from the starting allene, a process that may be conveniently fine tuned by addition of norbornene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…González 119 independently published their Au-catalyzed [2+2] cycloaddition of N -tosyl allenamides 446 with enol ethers 447 (Scheme 117) at the same time. Although the same gold complex was used as in Mascareñas’s report, catalyst loading was much lower, and more importantly, γ-substituted allenamides worked very well in this system to generate the cycloadduct such as 448c .…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…González 119 independently published their Au-catalyzed [2+2] cycloaddition of N -tosyl allenamides 446 with enol ethers 447 (Scheme 117) at the same time. Although the same gold complex was used as in Mascareñas’s report, catalyst loading was much lower, and more importantly, γ-substituted allenamides worked very well in this system to generate the cycloadduct such as 448c .…”
Section: Reactions Of Allenamidesmentioning
confidence: 99%
“…Multinuclear and multidimensional NMR studies revealed that 3 quickly dimerized to form disubstituted cyclobutanes (Supporting Information), as previously observed by Gonzaĺez. 21 The reaction was found to be catalytic since consecutive addition of 3 just increased the concentration of the product with no apparent modifications of the NMR spectra of 1OTf.…”
mentioning
confidence: 97%
“…This strategy allows the construction of complex heterocycle-fused and functionalized cyclobutanes (Scheme 24). 34, 35…”
Section: Cycloadditions Of Allenesmentioning
confidence: 99%